MOBILE ROBOT AUTONOMOUS NAVIGATION USING CRICKET INDOOR LOCATION SYSTEM - AB. AZIZ, AHMAD ASYRAF BIN (Universiti Teknologi PETRONAS, 2012)
A mobile robot has an ability to perform autonomous navigation in indoor environment when some information based on their current location was acquired. In order to perform navigation, the cricket indoor location system consists of transmitter and receiver was used in this project. This proposal describes how to integrate the cricket indoor location system with the mobile robot based on the current location from reference point. By using hardware/software design methodology, this project development was divided into two processes which are hardware design process and software design process. This project based on the embedded microcontroller, PIC located on the mobile robot process a signal from cricket indoor location system to perform the autonomous navigation. An event driven programming was used to ensure the correct event was executed based on input from sensor. Cricket indoor location system is a system that consists of several beacons and listeners to operate. As a conclusion, this proposal will demonstrate that integrated PIC and mobile robot, Stingray communicate with the cricket system to perform autonomous navigation.